Design, Synthesis, and Biological Evaluation of Chemically and Biologically Diverse Pyrroquinoline Pseudo Natural Products. Issue 9 (12th January 2021) - Liu, Jie; Cremosnik, Gregor S.; Otte, Felix; Pahl, Axel; Sievers, Sonja; Strohmann, Carsten; Waldmann, Herbert
Abstract: Natural product (NP) structures are a rich source of inspiration for the discovery of new biologically relevant chemical matter. In natural product inspired pseudo‐NPs, NP‐derived fragments are combined de novo in unprecedented arrangements. Described here is the design and synthesis of a 155‐member pyrroquinoline pseudo‐NP collection in which fragments characteristic of the tetrahydroquinoline and pyrrolidine NP classes are combined with eight different connectivities and regioisomeric arrangements. Cheminformatic analysis and biological evaluation of the compound collection by means of phenotyping in the morphological "cell painting" assay followed by principal component analysis revealed that the pseudo‐NP classes are chemically diverse and that bioactivity patterns differ markedly, and are dependent on connectivity and regioisomeric arrangement of the fragments. Abstract : Natural product (NP) fragments are combined in unprecedented arrangements to deliver a 155‐member pseudo‐NP collection. Cheminformatic analysis and biological evaluation of the collection by means of phenotyping in the morphological cell painting assay and principal component analysis revealed that the pseudo‐NP classes are chemically diverse with markedly different bioactivity patterns, which are dependent on connectivity and regioisomeric arrangement of the fragments.